Pengaruh Latihan Pogo Jump dengan Latihan Hand Up Squat Jump Terhadap Peningkatan Power Otot Tungkai - Permadi, Anggi Juni; Nursasih, Isna Daniyati; Rustiawan, Hendra (Universitas Galuh, 2023)
This study used a pre-experimental method with a two-group pretest-posttest design to determine how much causation from the pogo jump exercise with hand-up squat jumps had on increasing leg power. The population used was Panji Kusumah volleyball players, Tasikmalaya Regency, with a sample of 16-17-year-old students, totaling 20 people. Test the hypothesis using the t-test, namely paired sample t-test and independent sample t-test. Based on the hypothesis test -t count < -t table (-2.177 < -2.101) it is known that there is an average difference in the increase in leg power between the pogo jump exercise group and the hand up squat jump group on the increase in leg power in the study sample. The suggestions put forward are: 1) The form of pogo jump training with hand-up squat jumps can be used as material for physical condition training on the power component, 2) For further research, it is hoped that it will become a source of reference for other researchers so that research in the same field will continue to grow.